2021
DOI: 10.3389/fphar.2021.738630
|View full text |Cite
|
Sign up to set email alerts
|

Upper-Critical-Solution-Temperature Polymer Modified Gold Nanorods for Laser Controlled Drug Release and Enhanced Anti-Tumour Therapy

Abstract: Photothermal therapy (PTT) has become effective method for the treatment of malignant cancer. The development of PTT system with high anti-tumour effect is still the feasible research direction. Here, a new type of gold nanorods (AuNRs)-doxorubicin (DOX)/mPEG10K-peptide/P(AAm-co-AN) (APP-DOX) nano drug delivery system was proposed. Among them, AuNRs was used as high-efficiency photothermal agent. APP-DOX had a suitable size and can be targeted to accumulate in tumour tissues through circulation in the body. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 38 publications
(45 reference statements)
0
3
0
Order By: Relevance
“…[ 97 ] Similarly, controlled release of DOX can also be achieved with P(Am‐co‐AN). [ 98,99 ] Yang et al. reported a size‐shrinkable P(Am‐ co ‐AN)‐ g ‐PEG‐Lipoic acid (LA) micelles loaded with gold nanorods (AuNRs) and DOX for photothermal‐chemotherapy (Figure 6b).…”
Section: New Applications Of Ucst Polymersmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 97 ] Similarly, controlled release of DOX can also be achieved with P(Am‐co‐AN). [ 98,99 ] Yang et al. reported a size‐shrinkable P(Am‐ co ‐AN)‐ g ‐PEG‐Lipoic acid (LA) micelles loaded with gold nanorods (AuNRs) and DOX for photothermal‐chemotherapy (Figure 6b).…”
Section: New Applications Of Ucst Polymersmentioning
confidence: 99%
“…[97] Similarly, controlled release of DOX can also be achieved with P(Am-co-AN). [98,99] Yang et al reported a size-shrinkable P(Am-co-AN)-g-PEG-Lipoic acid (LA) micelles loaded with gold nanorods (AuNRs) and DOX for photothermal-chemotherapy (Figure 6b). [100] The AuNRs at the tumor site converted the light energy into heat, and the nanomicelles were split into a cascade of ultra-small micelles simultaneously.…”
Section: Photothermal Therapymentioning
confidence: 99%
“…The former is often explored to enhance the quantum efficiency and photostability of fluorophores, allowing the detection of lower quantities of biomarkers used in biosensing or bioimaging [32]. The latter is the foundation stone for the application of metallic nanoparticles in cancer hyperthermia/photothermal therapy [33]. However, it is essential to tailor the nanomaterials to interact specifically with near-infrared (NIR) radiation, a region of the spectra where the major biological components (e.g., collagen, hemoglobin, and water) have the lowest or insignificant absorption [34].…”
Section: Metallic Nanoparticles Applications and Therapiesmentioning
confidence: 99%
“…The higher blood circulation times associated with the utilization of these polymers will increase the nanomaterials' probability to accumulate and interact with the tumor cells, which can be essential for achieving superior antitumoral effects [64]. On the other hand, the natural and synthetic polymers can also imprint a stimuli-responsive (e.g., pH, temperature, and enzymatic) behaviour on the metallic-based nanomaterials, which can be particularly advantageous for controlling drug delivery [33,[65][66][67][68]. In this regard, the heat generated by the nanomaterials (e.g., PTT and magnetic hyperthermia) can be also explored to induce phase changes in the polymers (e.g., Poly(N-isopropylacrylamide) (PNIPAM)) or increase their solubility, which will trigger the drug release [68,69].…”
Section: Metal-polymer Based Nanomaterialsmentioning
confidence: 99%
“…[16] To address these issues, gold nanoparticles are often combined with other materials, inorganic (e.g., silica) and/or organic (e.g., polymers), to improve nanoparticles' biocompatibility, stability, and tumor specificity. [16][17][18][19] The typical metal-polymer hybrid structures (metal core-polymer shells or polymeric core-metal shells) are prepared by establishing covalent bonds or electrostatic interactions between the surface of the gold nanoparticles and the polymer's functional groups. [20,21] Nevertheless, the synthesis methodologies explored in the literature for creating metalpolymer hybrid structures are usually time-consuming, complicated, and involve multiple steps, which compromise the scalability and consequently the translation of gold-based nanomaterials into clinical practice.…”
Section: Introductionmentioning
confidence: 99%